Chemokines in Severe Cutaneous Adverse Reactions (SCARs) - Fumi Miyagawa; Hideo Asada (Biomolecules, 2021)
Although the incidence of severe cutaneous adverse reactions (SCARs) to medications is very low, SCARs can result in disability or even death if they are not diagnosed and treated properly. As the rapid recognition of SCARs is essential, it is necessary to develop diagnostic markers for them that can also be used to assess severity and predict outcomes in the early phase. In addition, it is important to identify novel therapeutic targets for SCARs. Chemokines are chemotactic cytokines that control the migratory patterns and locations of immune cells and usually exhibit markedly specific associations with certain human diseases. In Stevens-Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN), the Th1-associated chemokines chemokine (C-X-C motif) ligand 9 (CXCL9) and CXCL10 predominate, while in drug-induced hypersensitivity syndrome (DIHS)/drug reaction with eosinophilia and systemic symptoms (DRESS), the levels of the Th2-associated chemokines chemokine (C-C motif) ligand 17 (CCL17) and CCL22 are markedly elevated. We suggest that the distinct chemokine profiles of SJS/TEN and DIHS/DRESS can be used to aid their differential diagnosis. CXCL10 has also been reported to be associated with the development of long-term sequelae in DIHS/DRESS. This review focuses on the chemokines involved in the pathogenesis and adjuvant diagnosis of SCARs, particularly SJS/TEN and DIHS/DRESS, but also provides a brief overview of SCARs and the chemokine superfamily. As it is being increasingly recognized that an association exists between human herpesvirus 6 (HHV-6) and DIHS/DRESS, the possible roles of the chemokine/chemokine receptor homologs encoded by HHV-6 in the pathogenesis of DIHS/DRESS are also discussed.